Owners Ethnicity And Strategic Management Accounting - Antonius Singgih Setiawan; Rahmawati Rahmawati; Djuminah Djuminah; Ari Kuncara Widagdo (Jurnal Akuntansi, 2019)
This study aims to prove differences in the level of the role of accountant and the implementation of strategic management accounting based on ethnicity categories of hotel owners. The study is conducted with quantitative methods using primary data through a survey of hotel general managers/leaders in the Sumatra region. A total of 395 questionnaires are distributed to the hotel general managers/leaders. The number of questionnaires used in this study is 224. Mann-Whitney nonparametric tests for two independent samples analysis is used to test research hypotheses. The results of the study indicate that there are differences in the role of accountant and the implementation of strategic management accounting based on differences in ethnicity of the hotel owners.